2021
DOI: 10.1016/j.cegh.2021.100806
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and serum biochemistry parameters as a prognostic indicator of severally ill versus mild Covid-19 patients: A study from tertiary hospital in North India

Abstract: Background/objectives In, India coronavirus disease (COVID-19) cases are on the rise in terms of the total number of cases. Findings on clinical and hematological parameters alone carry no significance apart from telling patients present status and hence are diminutive. This study aims to assess the hematological and serum biochemistry parameters and correlate them with the presenting symptoms and severity of disease which can help predict the need for intensive care unit (ICU) care, help in triag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Dubey et al reported that calcium levels were lower in patients with mild symptoms but higher in patients with moderate symptoms. They did not detect abnormalities in the levels of sodium and potassium ions ( 52 ). Our study shows that the chloride ( p = 0.032) and calcium ( p = 0.032) ion levels are slightly lower in the positive group than in the negative group.…”
Section: Discussionmentioning
confidence: 99%
“…Dubey et al reported that calcium levels were lower in patients with mild symptoms but higher in patients with moderate symptoms. They did not detect abnormalities in the levels of sodium and potassium ions ( 52 ). Our study shows that the chloride ( p = 0.032) and calcium ( p = 0.032) ion levels are slightly lower in the positive group than in the negative group.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is slightly higher in women than in men (16). CRP value increases in patients with COVID-19 (17). Studies show that the amount of CRP in plasma increases due to inflammation in COVID-19 patients (18).…”
Section: Roc Analysismentioning
confidence: 95%
“…En particular, una disminución en el recuento de linfocitos, mostró ser un marcador importante entre los días 9 y 12 después de la admisión, que lo convirtió en un factor predictor de mal pronóstico para los pacientes. Por su parte, Dubey y colaboradores [5] en un hospital en India, evaluaron los parámetros hematológicos en 200 pacientes categorizados con infección leve, moderada y severa. El estudio mostró diferencias significativas en el recuento total de leucocitos (p=0,001), siendo la leucocitosis mayor en los pacientes con infección severa en comparación con los otros dos grupos, al igual que la linfopenia (p=0,001) y la relación leucocitos/neutrófilos (p=0,003), hallazgos similares a los encontrados por Yang y colaboradores [6] en un grupo de 78 pacientes con COVID-19, con excepción del recuento total de leucocitos, que no mostró diferencia significativa al comparar los resultados entre los diferentes grupos de pacientes.…”
Section: Parámetros Del Hemograma En Covid-19unclassified